Pharmacognosy Study of Guazuma ulmifolia Lam. Leaves - Rostinawati, Tina; Susilawati, Yasmiwar; Tjitraresmi, Ami; Zakia, Syifa; Nugrahani, Hanny; Ningrum, Sri Rahayu Widya; Kusumastuti, Pinastya Purwakaning; Sulistyaningsih, Widya Ayu (Indonesian Journal of Biological Pharmacy, 2025)
Guazuma ulmifolia Lam., commonly known as Jati Belanda, has been used extensively in traditional medicine because of its various pharmacological properties. This study aimed to evaluate the pharmacognostic features, phytochemical profile, and quality parameters of G. ulmifolia leaves. The dried leaves were extracted using 70% ethanol through maceration, and the extract was analyzed for organoleptic, microscopic, and macroscopic characteristics, moisture content, extractive values, ash content, metal contamination, and phytochemical composition. Phytochemical screening identified the presence of flavonoids, phenolics, saponins, coumarins, and monoterpenoids/sesquiterpenoids. Thin Layer Chromatography (TLC) confirmed the presence of flavonoids with quercetin as a standard. Quantitative analysis showed a total phenolic content of 2.1 ± 0.297 mg GAE/g and a total flavonoid content of 1.27 ± 0.12 mg QE/g of extract. All metal contamination levels, including Pb, Cd, and Hg, were within safe limits. These findings support the potential of G. ulmifolia leaves as a safe and standardized raw material for herbal medicine.Keywords:  Guazuma ulmifolia Lam., Pharmacognosy study, Phytochemical screening